Challenges in promoting HPV vaccine in the era of web 2.0: understanding the tricks and tropes of anti-vaccinologists - Steben, Marc (Brazilian Journal of Sexually Transmitted Diseases, 2022)
The National Geographic magazine cover from March 2015 issue states that there is a war on science: climate changes do not exist, evolution has never happened, moon landing was fake, genetically modified food is evil, and vaccinations can lead to autism. [...]